Rancang Bangun Sistem Irigasi Cerdas Menggunakan Metode Fuzzy Rule-Based untuk Otomatisasi Pintu Air dan Pendeteksian Endapan - Indra Hermawan Indra Hermawan; Dimas Aulia Fachrudin (Politeknik Caltex Riau, 2022)
Water is one of the keys to the success of rice farming. Rice fields that are always flooded can produce 5.92 tons per hectare while those that are not flooded only produce 4.80 tons per hectare. Irrigation channels that support the availability of water often experience problems such as silt deposits, water distribution based on estimates, and water theft. Therefore, the author proposes an intelligent irrigation system that is able to automate the control and supervision of floodgates through the internet network. The result of this research is a prototype system that can work well, with an average measurement error of 2.1% by ultrasonic sensors, and the conductivity of water flow with silt is above 641 points. Radio-based communications and TCP/IP require lower operational costs than SMS-based GSM methods. Radio-based technology and TCP/IP can save operating costs by 97.5% compared to GSM technology. The system is also capable of sending 16 data to the server in one minute. Overall, the system has worked well to automate the floodgates, and detect sludge.